Education and training in preservation and conservation of cultural heritage materials: whither Nigeria? (2013)
Libraries, archives and museums, particularly those in the tropics, arc faced with the challenge of material deterioration. This constitutes a big threat to access to the invaluable heritage materials maintained by these institutions. One way of tackling the problem is to have qualified and highly skilled human resources in preservation and conservation. Knowledge and skills in preservation and conservation can be acquired only through education, training and re-training. This paper, therefore, examines the place of education and training in preservation and conservation in the survival of cultural heritage materials. It makes a survey of educational institutions around the world offering courses in heritage materials conservation. It zeros in on Nigeria, examines the training facilities available in the country and concludes that much still needs to be desired. Finally, it makes a case for the establishment in Nigeria of a centre of excellence Tor the preservation and conservation of heritage materials.